Pengaruh Model Pembelajaran Aptitude Treatment Interaction (Ati) Dengan Minat Terhadap Kreatifitas Membuat Karya Seni Rupa Dua Demensi Siswa Kelas X Tik Smkn 1 Kamal Bangkalan - Ratnawati, Dwi Ema; Kusmiati; Sunardjo (Penerbit STKIP PGRI Bangkalan, 2024)
This research aims to examine the effect of applying the Aptitude Treatment Interaction (ATI) learning model on students' interest and creativity in creating two-dimensional works of art. This research is motivated by the importance of learning approaches that are adapted to individual student characteristics to increase motivation and learning outcomes. This research used a quasi-experimental research design with two groups, namely the experimental group taught using the ATI model and the control group taught using conventional methods. The research sample was students of class X IK SMKN 1 Kamal Bangkalan who were chosen randomly. Data collection was carried out through interest questionnaires, creativity tests, and observations. The research results showed that there were significant differences between the experimental group and the control group in terms of 1 interest and creativity in making two-dimensional works of art. Students taught using the ATI model show higher interest in learning and produce more creative work compared to students taught using conventional methods. Based on the research results, it can be concluded that the ATI learning model is effective in increasing students' interest and creativity in creating two-dimensional works of art. Therefore, it is recommended that fine arts teachers can apply the ATI learning model in the learning process to improve the quality of learning and student work results